Cardiovascular outcomes with an inhaled beta2-agonist/corticosteroid in patients with COPD at high cardiovascular risk. Issue 19 (17th April 2017) - Brook, Robert D; Anderson, Julie A; Calverley, Peter MA; Celli, Bartolome R; Crim, Courtney; Denvir, Martin A; Magder, Sheldon; Martinez, Fernando J; Rajagopalan, Sanjay; Vestbo, Jørgen; Yates, Julie; Newby, David E
Abstract : Objectives: Cardiovascular disease (CVD) and chronic obstructive pulmonary disease (COPD) often coexist. We assessed the effect of inhaled COPD treatments on CVD outcomes and safety in patients with COPD and at heightened CVD risk. Methods: The SUMMIT (Study to Understand Mortality and MorbidITy) was a multicentre, randomised, double-blind, placebo-controlled, event-driven trial in 16 485 patients with moderate COPD who had or were at high risk of CVD. Here, we assessed the prespecified secondary endpoint of time to first on-treatment composite CVD event (CVD death, myocardial infarction, stroke, unstable angina or transient ischaemic attack (TIA)) by Cox regression and by clinician-reported CVD adverse events across the four groups: once-daily inhaled placebo (n=4111), long-acting beta2 -agonist (vilanterol (VI) 25 µg; n=4118), corticosteroid (fluticasone furoate (FF) 100 µg; n=4135) and combination therapy (FF/VI; n=4121). Results: Participants were predominantly middle-aged (mean 65 (SD 8) years) men (75%) with overt CVD (66%). The composite CVD endpoint occurred in 688 patients (first event: sudden death (35%), acute coronary syndrome (37%) and stroke or TIA (23%), and was not reduced in any treatment group versus placebo: VI (HR 0.99, 95% CI 0.80 to 1.22), FF (HR 0.90, 95% CI 0.72 to 1.11) and their combination (HR 0.93, 95% CI 0.75 to 1.14). Outcomes were similar among all subgroups. Adverse events, including palpitations and arrhythmias, did not differ by treatment. Conclusions: In patients with COPD with moderate airflow limitation and heightened CVD risk, treatment with inhaled VI, FF or their combination has an excellent safety profile and does not impact CVD outcomes. Trial registration number: NCT01313676.